Limited AT1 Receptor Internalization Is a Novel Mechanism Underlying Sustained Vasoconstriction Induced by AT1 Receptor Autoantibody From Preeclampsia. Issue 6 (19th March 2019) - Bian, Jingwei; Lei, Jinghui; Yin, Xiaochen; Wang, Pengli; Wu, Ye; Yang, Xiaoli; Wang, Li; Zhang, Suli; Liu, Huirong; Fu, Michael L. X.
Abstract : Background: Angiotensin II type 1 receptor (AT1 R) autoantibody (AT1‐AA) was first identified as a causative factor in preeclampsia. Unlike physiological ligand angiotensin II (Ang II), AT1‐AA can induce vasoconstriction in a sustained manner, causing a series of adverse effects, such as vascular injury and poor placental perfusion. However, its underlying mechanisms remain unclear. Here, from the perspective of AT1 R internalization, the present study investigated the molecular mechanism of sustained vasoconstriction induced by AT1 R autoantibody. Methods and Results: In the current study, we used the vascular‐ring technique to determine that AT1‐AA‐positive IgG, which was obtained from the sera of preeclamptic patients, induced long‐term vasoconstriction in endothelium‐intact or endothelium‐denuded rat thoracic arteries. The effect was caused by prolonged activation of AT1 R downstream signals in vascular smooth muscle cells, including Ca 2+, protein kinase C, and extracellular signal‐regulated kinase 1 and 2. Then, using subcellular protein fractionation, cell surface protein biotinylation, and total internal reflection fluorescence, we found that AT1‐AA‐positive IgG resulted in significantly less AT1 R internalization than in the Ang II treatment group. Moreover, through use of fluorescent tracing and bioluminescence resonance energy transfer, we found that AT1‐AA‐positive IgG cannot induce the recruitment of β‐arrestin1/2, which mediated receptor internalization. Then, the effect of sustained AT1 R activation induced by AT1‐AA‐positive IgG was rescued by overexpression of β‐arrestin2. Conclusions: These data suggested that limited AT1 R internalization resulting from the inhibition of β‐arrestin1/2 recruitment played an important role in sustained vasoconstriction induced by AT1‐AA‐positive IgG, which may set the stage for avoiding AT1 R overactivation in the management of preeclampsia.